Should doctors support restrictions on anti-abortion protests?. (9th November 2017) - Robinson, Francesca
Abstract : The idea of buffer zones to prevent picketing around abortion clinics is gaining traction. Francesca Robinson reports on the feelings of doctors on both sides of the fence